Modelling the climate sensitivity of proso millet (panicum miliaceum L.) in Sri Lanka. - Wimalasiri, G. E. M. (2019)
Proso millet (Panicum miliaceum L.) is a minor cereal cultivated as a subsistence crop in Africa and Asia. It is an essential crop in rainfed farming systems of dry areas in Low Country Sri Lanka where rainfall is the limiting factor for crop production. The crop’s shorter lifespan, low water requirement and considerable yield in unfavourable environments are important adaptive features. It shows promise for high nutrient content and yield under marginal environmental conditions and is suggested as a crop that might be less affected by climate change. Proso millet in Sri Lanka is cultivated from local accessions/landraces as there are no varieties bred for specific traits. There is ample evidence to suggest that Sri Lanka's climate has already changed, and its agricultural sector is vulnerable to climate shocks. Therefore, it is important that these minor millets should receive research attention, which is the reason for selection of the crop. This study was designed to analyse the current status of Proso millet cultivation in Low Country Dry Zone Sri Lanka and to model the sensitivity of yield to climate change in mid-21st century through crop-climate modelling.